Optimum level of spray-dried porcine plasma for early-weaned (10.5 d of age) starter pigs - Owen, K.Q.; Dritz, Steven S.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 290 early-weaned pigs (initially 7.6 lb and 10.5 d of age) was used to evaluate various levels of spray-dried porcine plasma. Pigs were assigned to one of five experimental diets with either 5, 7.5, 10, 12.5, or 15% spray-dried porcine plasma replacing dried skim milk. Pigs were fed this diet for the first 14 days postweaning. Common diets were fed from d 14 to 42 postweaning in order to monitor subsequent performance. During the first phase (d 0 to 14 postweaning), linear improvements in average daily gain (ADG) and average daily feed intake (ADFI) occurred as the level of spray-dried porcine plasma increased from 5% to 15%. This resulted in a linear improvement in weight at d 14 postweaning. For the first phase and subsequent phases, no differences occurred in feed efficiency (F/G). From d 14 to 21 postweaning, a linear decrease occurred in ADG and ADFI as well as a linear deterioration of F/G as the level of spray-dried porcine plasma increased from 5% to 15%. This reversal of performance resulted in no difference of pig weights at d 21 and 25 postweaning. From d 25 to 42 postweaning, no difference was seen in ADG. In summary, spray-dried porcine plasma can be used as an effective replacement for dried skim milk as a protein source in diets for pigs weaned at 10 d of age.
Keywords: Swine; Starter; Spray-dried porcine plasma; Skim milk